Three phytoparasitic species of Periconiella from Indian subcontinent - and SANJAY K. SINGH, ARCHANA SINGH, KIRTI BHALLA (Indian Phytopathology, 2002)
Three hitherto unknown species of Periconiella Sacc.,P. litseae sp. nov., P. lygodii sp. novo and P. mesoneuri-cuculati sp. nov., collected on Litsea chinensis (Lauraceae), Lygodium flexuosum (Schizaeaceae) and Mesoneurum cuculatum (Fabaceae) respectively, are described, illustrated and compared with allied taxa. The former was collected from Kathmandu valley, Nepal, later two from North-Eastern, U.P., India.